Lipid Profile Changes in Toxoplasmosis Aborted Women (Baghdad Science Journal, 2013)
Blood lipids are important mediators of host defense during the acute phase of innate immunity. Parasites may induce significant changes in lipid parameters, as has been shown in vitro study where substitution of serum by lipid/cholesterol in medium and in experimental models (in vivo). Thus changes in lipid profile occur in patients that having active infections with most of the parasites. Toxoplasma cannot synthesize cholesterol and depends upon acquisition of low density lipoprotein (LDL)-derived from the host cell, via endocytosis mediated by the LDL receptor or the LDL receptor-related protein.The present study is conducted to evaluate the changes in lipid profile in T. gondii infected women.A total of patients included 87 aborted women who had positive test for toxoplasmosis and a two control groups (115 non toxoplasmosis women): The first control group (negative control) contains 88 apparently healthy women and the second control group (positive control) contains 87 aborted women, were registered from Al-Yarmouk Teaching Hospital in Baghdad. Both control groups had negative test for toxoplasmosis. These samples were collected between the period January 2009 and May 2010. Patients and controls women's had comparable age that ranged between 15-45 years old. Serum samples were collected from each woman in the three groups and then the Enzyme Linked Immunosorbant Assay (ELISA) and Lipid profile assays were performed by using two commercial kits. In the basis of ELISA test anti-T. gondii antibodies (IgG and IgM), detected in the patients sera, three types of toxoplasmosis were identified. These were; acute type, sub-acute type and chronic type. Most of patients had chronic type 75 (86.2%). There were significant decreased in the total cholesterol are 165.05 (control groups 212.44, 213.33 respectively), triglycerides 134.98 (control groups 173.81, 174.40 respectively), LDL 87.78 (control groups 137.32, 135.87 respectively) and vLDL values 26.99 (control groups 34.70, 34.60 respectively). In contrast, there was significant increased in HDL value (49.0) as compared with control groups (40.42, 38.78 respectively). Also the result indicated that there were no significant differences in lipid profile values between the three types of disease.Toxoplasma gondii had a role in changes lipid profile values in infected women which characterized by decrease in cholesterol and triglyceride and LDL with a significant increases in HDL level. Further studies needed to maintain the effect of duration of the toxoplasmosis (acute or chronic) on the changes in lipid profile.